Early management of adults with an uncomplicated first generalised seizure. Issue 4 (23rd March 2005) - Dunn, M J G; Breen, D P; Davenport, R J; Gray, A J
Abstract : A literature review of first seizures in adults was performed and a management algorithm was constructed. This review highlights the importance of a thorough history and examination, routine biochemistry and haematology, an electrocardiogram, selected neuroimaging, discharge planning with driving and lifestyle advice, and follow-up in a specialist clinic.